MIRERC-A 083/2025: [Amendment]Identifying Breast Cancer Genetic Risk Factors in Kenya (BreCXome) - Onyambu, Dr. Frank; Mwale, Job; Bediako, Yaw; Kibengo, Chege; Amoako, Emmanuella; Paemka, Lily; Abdihamid, Omar (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
Per GLOBOCAN 2020, breast cancer has surpassed lung cancer as the most diagnosed cancer worldwide. In most parts of Africa, breast cancer is the leading cause of cancer deaths among women. Although cancers present with racial disparities that are largely influenced by genetic factors, there is a significant dearth of genetic studies in Sub-Saharan Africa in general. Globally, patients of African descent suffer the shortest survival rates and poorest outcomes. Due to considerable difference in linkage disequilibrium structure between African and Caucasian populations, largely Eurocentric research data are not representative of African people. African genomes are the most diverse and therefore the most likely to reveal the genetic basis of complex human traits. Despite this immense potential, there is a profound paucity of African cancer genomic data. Due to the dearth of genetic studies conducted among people of African descent, the proposed study presents an opportunity to identify novel variants. The pathogenesis of breast cancer remains largely unexplained; therefore, the objective of the proposed study is to identify genes and pathways underpinning breast cancer pathogenesis in a Kenyan cohort. The long-term goal is to provide a comprehensive genetic landscape of breast cancer in Black Africans and develop resources for novel molecular diagnostics and therapeutics. Study samples will be obtained from The Meru Teaching and Referral Hospital and various laboratories that offer histopathology services in Kenya. The proposed study will have both retrospective and prospective arms. In the retrospective arm, we will retrieve data for all breast cancer cases from the medical records and utilize available archived breast cancer FFPE samples whereas in the prospective arm, we will collect blood and breast cancer tumor samples (i.e., FFPE). Genomic or cell-free DNA isolated from the FFPEand blood will be subjected to whole genome sequencing and bioinformatics analyses to identify novel loci and elucidate pathways associated with breast cancer pathogenesis among Black Africans. This study also aims to create a comprehensive breast cancer database by integrating data from breast cancer cases into a cloud-based clinical data management application (Uvosyo). This streamlined approach will allow efficient organization and retrieval of information, offering valuable insights into breast cancer trends, treatment outcomes, and patient profiles. Ultimately, this will lead to more informed decision-making and improved patient care.